Internet connectivity disruption in Ethiopia (Ethiopia) - Voidly (2026)
CRITICAL severity disruption detected in Ethiopia. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: ET-2026-0064
Keywords: internet disruption; ET; disruption; critical